2022
DOI: 10.1073/pnas.2209304119
|View full text |Cite
|
Sign up to set email alerts
|

SMC protein RecN drives RecA filament translocation for in vivo homology search

Abstract: While the molecular repertoire of the homologous recombination pathways is well studied, the search mechanism that enables recombination between distant homologous regions is poorly understood. Earlier work suggests that the recombinase RecA, an essential component for homology search, forms an elongated filament, nucleating at the break site. How this RecA structure carries out long-distance search remains unclear. Here, we follow the dynamics of RecA after induction of a single double-strand break on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Distant ssDNA sites are thus spatially associated and at a null distance from the resection front in the absence of Rad51. These observations show that Rad51 extends the ssDNA molecule in WT cells, which otherwise collapses upon RPA binding in rad51Δ cells ( Figure 3E ), an interpretation consistent with globular RPA-ssDNA structures and elongated Rad51/RecA-ssDNA structures observed in vitro and in cells 14,16,1821,48,5054 . Consequently, stiffening of ssDNA by Rad51 projects DSB-proximal sites away from the DSB-borne chromatin environment, which promotes genome-wide homology search ( Figure 3E ).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Distant ssDNA sites are thus spatially associated and at a null distance from the resection front in the absence of Rad51. These observations show that Rad51 extends the ssDNA molecule in WT cells, which otherwise collapses upon RPA binding in rad51Δ cells ( Figure 3E ), an interpretation consistent with globular RPA-ssDNA structures and elongated Rad51/RecA-ssDNA structures observed in vitro and in cells 14,16,1821,48,5054 . Consequently, stiffening of ssDNA by Rad51 projects DSB-proximal sites away from the DSB-borne chromatin environment, which promotes genome-wide homology search ( Figure 3E ).…”
Section: Resultssupporting
confidence: 84%
“…A conserved property of RecA-family proteins is to polymerize on DNA into elongated structures exhibiting persistence length orders of magnitude greater than protein-free ssDNA in vitro 2 . Such structures were recently observed in bacterial and S. cerevisiae cells using fluorescently-tagged RecA/Rad51 proteins 18,20,21 . Our ssHi-C data and modeling support the proposal from these cytologic studies that the possibility of genome-wide homology search lies in NPF’s atypical, rigid structure.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The key function of the SMC-like protein RecN is the displacement of the RecA inside the cell through its ATPase activity. It has been shown that in the absence of the RecN, the RecA filament is not able to significantly move within the cell, and also the removal of the ATPase activity of RecN leads to blocking the movement of RecA into bacteria [6]. It is also known that RecN stimulates the ligation of linear duplex DNA molecules [7] and stimulates RecA-mediated DNA strand exchange [8].…”
mentioning
confidence: 99%